CircLPAR3 knockdown suppresses esophageal squamous cell carcinoma cell oncogenic phenotypes and Warburg effect through miR-873-5p/LDHA axis. (25th November 2022) - Cheng, Yao; Ma, Zhenchuan; Liu, Shiyuan; Yang, Xiaoping; Li, Shaomin
Background: Circular RNAs (circRNAs) have been identified to participate in regulating multiple malignancies. Herein, this study aimed to explore the clinical significance, biological function, and regulatory mechanisms of circRNA lysophosphatidic acid receptor 3 (circLPAR3) in esophageal squamous cell carcinoma (ESCC) cell malignant phenotypes and Warburg effect. Methods: The qRT-PCR and Western blot were used to detect the levels of genes and proteins. Glucose uptake and lactate production were detected to determine the Warburg effect. The effects of circLPAR3 on ESCC cell proliferation, apoptosis, and metastasis were evaluated by MTT, 5-ethynyl-2′-deoxyuridine (EdU), flow cytometry, wound healing, and transwell assays. The binding interaction between miR-873-5p and circLPAR3 or lactate dehydrogenase A (LDHA) was verified using dual-luciferase reporter and RIP assays. Xenograft mice models were established to conduct in vivo analysis. Results: CircLPAR3 is a stable circRNA and was increased in ESCC tissues and cells. Functionally, circLPAR3 knockdown suppressed ESCC cell Warburg effect, proliferation, metastasis, and induced apoptosis in vitro, and impeded xenograft tumor growth and Warburg effect in ESCC mice models. Mechanistically, circLPAR3 served as a sponge for miR-873-5p, which targeted LDHA. Moreover, circLPAR3 could regulate LDHA expression by sponging miR-873-5p. Thereafter, rescue experiments suggested that miR-873-5p inhibition reversed the anticancer effects of circLPAR3 silencing on ESCC cells. Furthermore, miR-873-5p overexpression restrained ESCC cell Warburg effect and oncogenic phenotypes, which were abolished by LDHA up-regulation. Conclusion: CircLPAR3 knockdown suppressed ESCC cell growth, metastasis, and Warburg effect by miR-873-5p/LDHA axis, implying a promising molecular target for ESCC therapy.